Validade e reprodutibilidade do questionário de frequência alimentar online com suporte de imagens da coorte de universidades mineiras ( PROJETO CUME) - Heloisa Gambarelli de Araújo Azarias (2020)
Introduction: Food consumption evaluation has been commonly used in epidemiological studies since it correlates with health and chronic non-communicable diseases. Objectives: To describe the construction of the online Food Frequency Questionnaire (FFQ) used at CUME (Cohort of Universities of Minas Gerais, Brazil) and evaluate its validity and reproducibility. Methods: FFQ construction was based on an original version previously validated for the Brazilian population, together with a photographic album. The FFQ was answered twice in one year (March/August 2018 – March/April 2019; n = 108 participants – reproducibility) and two 24-hour dietary recall (24hR) were applied in two seasons of the southern hemisphere in 2018 (autumn and winter; n = 150 participants – validity), totaling four 24hR per participant. To assess the validity and reproducibility, the intraclass correlation test (ICC) was applied and agreement percentages of total energy consumption, nutrients and food groups (nutritional similarity and industrial processing degree) were calculated after categorization by tertiles. Results: The elaborated FFQ had 144 food items separated into eight groups (dairy products; meat and fish; cereals and legumes; fruits; vegetables; fats and oils; drinks; other foods), 96 photographs of food and 5 photographs of utensils. In assessing validity, ICCs for energy and macronutrients were considered moderate, ranging from 0.41 (energy) to 0.59 (protein); for the other items evaluated, ICCs were considered low to moderate, ranging from 0.25 (fibers) to 0.65 (vitamin B6). All percentages of exact + adjacent agreement were greater than 80%. In assessing reproducibility, ICCs for energy and all assessed items were considered moderate to excellent, ranging from 0.60 (vegetables) to 0.91 (vitamin E and retinol), with an average exact + adjacent agreement percentage of 92.5%. Conclusion: CUME project’s online and self-completed FFQ had satisfactory validity and reproducibility, and can be used to analyze the association between food consumption and chronic non-communicable diseases in adults with a high level of education.